2019
DOI: 10.1155/2019/1872134
|View full text |Cite
|
Sign up to set email alerts
|

JinQi Jiangtang Tablet Regulates Gut Microbiota and Improve Insulin Sensitivity in Type 2 Diabetes Mice

Abstract: Background Gut microbiota modulates the barrier function and host inflammatory state in metabolic disease. JinQi Jiangtang (JQJT) tablets are a traditional Chinese medicine for the treatment of diabetes. However, the low bioavailability of its chemical compositions makes it hard to explain the pharmacological mechanisms. Method Diabetic mice were orally treated with JQJT tablets for 5 weeks. Fasting blood glucose and the level of HbA1c were measured, and ITT were conducted to determine the insulin improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Pharmacological investigations indicated that TCPMs present beneficial effects on reducing body weight, enhancing insulin sensitivity, protecting β-cells, improving insulin secretion, correcting glucose and lipid metabolism disorders, and improving the microcirculation and the immune system. [ 5 6 7 8 9 10 11 12 13 ] For example, the Tianmai Xiaoke tablet which contains of Schisandra Chinensis, Ophiopogon Japonicus, Trichosanthis Radix and Chromium Picolinate is approved by the State Food and Drug Administration of China (state medical license number Z20049007) can decrease FBG and HbA1c levels in T2DM patients. [26] In addition, some studies demonstrated that Tianmai Xiaoke tablets could down-regulate PTP1B and PCK2 by activating the insulin signaling pathway, thereby reducing the HbA1c level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological investigations indicated that TCPMs present beneficial effects on reducing body weight, enhancing insulin sensitivity, protecting β-cells, improving insulin secretion, correcting glucose and lipid metabolism disorders, and improving the microcirculation and the immune system. [ 5 6 7 8 9 10 11 12 13 ] For example, the Tianmai Xiaoke tablet which contains of Schisandra Chinensis, Ophiopogon Japonicus, Trichosanthis Radix and Chromium Picolinate is approved by the State Food and Drug Administration of China (state medical license number Z20049007) can decrease FBG and HbA1c levels in T2DM patients. [26] In addition, some studies demonstrated that Tianmai Xiaoke tablets could down-regulate PTP1B and PCK2 by activating the insulin signaling pathway, thereby reducing the HbA1c level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism was related to increasing the gut barrier function and reducing the host inflammatory reaction. [29] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbes are critical for intestinal epithelial barrier function and for the maintenance of physiological homeostasis; the gut microbiota is a promising therapeutic target for diabetes and its complications, as it plays a signi cant role in the related pathogenic processes [31]. Previous studies have shown that the αdiversity of the gut microbiota is connected with obesity and diabetes [32]. According to previous research, the α-diversity in mice with diabetic cardiomyopathy was decreased, but this decrease can be reversed by pyridostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of studies have shown that TCM has the capacity of lowering blood glucose, improving inflammation and modulating gut microbiota. [ 11 13 ] Chinese herbal medicine (CHM), the main component of TCM, is usually rich in fiber and phytochemicals. When an anti-diabetic CHM is taken orally, its bioactive components are absorbed in the intestine and change the composition of gut microbiota, including inhibiting pathogens such as Escherichia coli , and promoting beneficial bacteria such as Adlercreutzia, Alloprevotella , Fecalibacterium prausnitzii , Lactobacillus, and Bifidobacterium .…”
Section: Introductionmentioning
confidence: 99%